Thermal Management of Li-ion batteries by Thermal Barrier Coatings - Kumaresan, Nagarajan (My University, 2021)
Electrification is the new normal of the upcoming world. Electrified vehicles require a system to store the electrical energy and Li-ion battery systems are one of the top contenders for energy storage because of their high power densities and repeatability in charging and discharging of the battery. Need for increasing the efficiency of the Li-ion batteries requires close packing of the cells in the battery which results in difficulties in thermal management of the Li-ion batteries. The objective of the thesis work is to experimentally verify if Thermal Barrier Coatings (TBC) can be used for preventing the thermal propagation in the Li-ion batteries and thereby stopping the accidents in electric vehicles owing to Thermal Runaway (TR). Yttria Stabilised Zirconia (YSZ) is coated on aluminium plates by Atmospheric Plasma Spraying (APS) and Suspension Plasma Spraying (SPS). The two coatings are tested thermally and mechanically, and the results are compared. APS coating shows better mechanical properties due to the presence of the polymer filling the pores in the coating whereas, the SPS coating shows better thermal properties.
Keywords: Atmospheric Plasma Spraying (APS); Suspension Plasma Spraying (SPS); YSZ; Thermal Runaway